The purified yeast pre-mRNA splicing factor PRP2 is an RNA-dependent NTPase. - Kim, S H (1992)
Unlike autocatalyzed self-splicing reactions, nuclear pre-mRNA splicing requires transacting macromolecules and ATP. A protein encoded by the PRP2 gene of Saccharomyces cerevisiae is required, in conjunction with ATP, for the first cleavage-ligation reaction of pre-mRNA splicing. In this study, we have purified two forms of the PRP2 gene product with apparent molecular weights of 100 kDa and 92 kDa, from a yeast strain overproducing the protein. Both proteins were indistinguishable in their ability to complement extracts derived from a heat-sensitive prp2 mutant. Furthermore, we show that the PRP2 protein is capable of hydrolyzing nucleoside triphosphates in the presence of single-stranded RNAs such as poly(U). However, purified PRP2 by itself did not unwind double-stranded RNA substrates. The fact that an RNA-dependent NTPase activity is intrinsic to PRP2 may account for the ATP requirement in the first catalytic reaction of pre-mRNA splicing.